Prognosis of ulcerative colitis-associated colorectal carcinoma compared to sporadic colorectal carcinoma: a matched pair analysis - Leowardi-Bauer, Christine; Schneider, Marie-Luise; Hinz, Ulf; Harnoß, Jonathan M.; Tarantino, Ignazio; Lasitschka, Felix; Ulrich, Alexis; Büchler, Markus W.; Kadmon, Martina (Annals of surgical oncology, 2016)
Ulcerative colitis (UC) patients have an increased risk of developing colorectal carcinoma (CRC). In contrast to clinical and pathogenetic differences, little is known about how prognosis compares between these patients and those with sporadic CRC. The aim of this study was to compare their characteristics and prognosis and identify independent risk factors for patients with UC-associated CRC.